Multilingualism and Indigenous School Education in Brazil: past, present and future challenges - de Oliveira, Carolina Miranda; Figueira-Cardoso, Samuel (Multilingual Margins: A journal of multilingualism from the periphery, 2023)
In Brazil, only with the Federal Constitution of 1988 is indigenous peoples guaranteed the right to use their languages and cultures. However, since colonization, many languages have disappeared. The number of speakers of these languages has decreased, and different stages and language policies have promoted the Portuguese language at the expense of indigenous languages. All these factors to different sociolinguistic situations, current challenges in language teaching and learning, as scenarios of monolingualism in an indigenous language, continuum bilingualism, and non-speaking communities of an indigenous language. However, with revitalization, actions occur in the Brazilian context. We resorted to assumptions derived from studies on multilingualism, language policy, and language pedagogies. Based on these assumptions, this article aims to reflect on the moments and movements of indigenous school education and language policies in Brazil’s multilingual and multicultural country. This study is qualitative interpretive research based on a literature review in an integrative approach of theoretical perspectives concerned with the topic.